(3fNH ef WHbGJ GdTGaYjI GdcHQis - (3eLghds; (3JGL GdOjf GdSHcj , CHh fUQ,J (B771 (3g` s
(3ChdgG (B:s
(3dbGVi GdbVGI eMeO Hf YHOGdQMef GdaShi, GdeJhaj SfI (B478: (3ef QGe Yf GdEdg efRdI adjWY Gddg Mb WGYJg hMb WGYJg GdbjGe HgG eHGdZG ajg hSY WGbJg s
(3BNQgG (B:s
(3HBNQg HQfGeL GdLRA GdChd ef GdfNH, hHQfGeL GdLR GdKGfj s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B184 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B225s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B444 s
Keywords: (3GdJGQjNs